2022
DOI: 10.1097/md.0000000000032149
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic ultrasound alone or in combination with tracheal amylase as a tool predictor of ventilator-associated pneumonia in neurocritical patients

Abstract: In this study, we aim to evaluate whether thoracic ultrasound (TUS) and tracheal amylase (TA) alone or in combination can predict the development of ventilator-associated pneumonia (VAP) in neurocritical patients. Consecutive adult patients with neurocritical disease with normal chest radiographs who required intensive care unit admission and mechanical ventilation between March 2015 and July 2018 were included. TUS and Amylase levels were measured during the first 24 hours and repeated 48 hours after orotrach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…After deduplication and precluding irrelevant records, we carefully reviewed the full text of 11 candidate studies. Finally, six studies [10,[19][20][21][22][23] met the eligibility criteria and were included in the quantitative analysis. Figure 1 shows the study selection process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After deduplication and precluding irrelevant records, we carefully reviewed the full text of 11 candidate studies. Finally, six studies [10,[19][20][21][22][23] met the eligibility criteria and were included in the quantitative analysis. Figure 1 shows the study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, no further clinical studies have been conducted to con rm above ndings until Weiss et al [10] revealed the signi cance of bronchoalveolar lavage amylase in diagnosing and differentiating VAP with high sensitivity and negative predictive value. After that, the bronchial amylase as a maker for predicting or diagnosing VAP has been extensively studied [19][20][21][22][23]39], but the results are con icting. In the present systematic review and meta-analysis, we showed that bronchial amylase can be useful as a potential marker for early detection of VAP in clinically.…”
Section: Discussionmentioning
confidence: 99%